Aggressive Rhetoric: Prosodic and Kinetic Means - Petlyuchenko, Nataliya V.; Artiukhova, Anna (University of Nantes, 2015)
This paper deals with the definition of aggressive rhetoric as the persuasive method in political communication, the transformation of the concept 'speech aggression' towards its positive semantic, the complex of aggressive speech means on the verbal and paraverbal levels. Verbal means of an aggressive rhetoric are the rhetorical figures, such as the antithesis that creates the greatest emotional stress due to its underlying semantic contrast. Paraverbal means of aggressive rhetoric are the prosody and co-speech gestures of the antitheses.
Petlyuchenko N. Aggressive Rhetoric: Prosodic and Kinetic Means / N. Petlyuchenko, A. Artiukhova // Gesture and Speech in Interaction 4th edition. - Nantes, 2015. - P. 191-194.
Keywords: political communication; aggressive rhetoric; rhetorical figures; antithesis; verbal; prosodic; kinetic; политическая коммуникация; агрессивная риторика; риторические выражения; антитезис; вербалика; просодика; кинесика; політична комунікація; агресивна риторика; риторичні вирази; антитеза; вербаліка; просодика; кінесика